The Women-Floggers of St Marylebone: A Study of Punishment and Abuse in the Victorian Workhouse. - James, Jeff (London Journal, 2023)
This article examines punishment, agency, and abuse in Victorian workhouses. The article builds on recent research on punishment in mostly rural workhouses, with a study of the punishment of young women in the metropolitan workhouse of St Marylebone. It complements David Green's research into discipline and unrest in London workhouses and builds on Alysa Levene's work on St Marylebone under the Old Poor Law. Local and national sources are confected to highlight different perspectives, providing a deeper and more holistic understanding of abuse in the workhouse, through the prisms of punishment and agency. In doing so, the article addresses critical gaps in the historiography of the New Poor Law in London and more widely. Specifically, it argues that the understanding of punishment has, to date, been too simplistic and suggests that it is useful to reconceptualise punishment as a matrix, where anyone could be punished, including officials, and where everyone had, to some extent, agency.